PEDAGOGICAL STRATEGIES FOR IMPROVING THE IMMUNITY OF FUTURE RELIGIOUS SPECIALISTS AGAINST “MASS CULTURE” BASED ON A GENDER APPROACH (International Conference on Modern Science and Scientific Studies, 2025)
In modern times, the influence of mass culture is felt by everyone, from young children to adults. Its impact extends to all spheres of society, uniting people in various corners of the world while simultaneously causing individualism, differentiation, and conflict. The influence of mass culture on religious and moral aspects is particularly important and pressing. This article discusses the impact of mass culture on religion and religious education, as well as pedagogical strategies for developing immunity against this influence. We will explore approaches that future religious specialists can implement in this regard.